Optimalisasi Stabilitas Lereng pada Daerah Sempadan Sungai Santer Kecamatan Gumukmas Kabupaten Jember - Moch. Wahyudi Riskyanto; Paksitya Purnama Putra; Luthfi Amri Wicaksono (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
The Santer Riverbank which is located in Panggul Melati Hamlet, Kepanjen Village, Gumukmas District, Jember Regency, East Java is still used by the community for agricultural land. This research was conducted to create safe agricultural land for the community. Landslides on this riverbank often occur because it is located on the edge of the river and has a steep slope. In the observation in 2022, there is a collapsed riverbank approximately 20 meters in front of the river embankment. To prevent a longer landslide area, the slopes on the river border are optimized so that residents can still use the land safely. The selected reinforcement is made based on the geometric conditions and the results of the SF value from modeling the existing conditions using the Geostudio program. Appropriate reinforcement based on geometric conditions and SF values ​​is a balancing method. close to the counterweight method, the geometric conditions are more optimal with the SF value increasing from 1.099 to 1.623